Prospects for application of phytopreparations in the complex treatment of type 2 diabetes mellitus - Rybak, Viktoria; Maloshtan, Ludmila; Korol, Victoria (PC Тесhnology сеntеr, 2021)
Diabetes mellitus (DM) occupies an important place in the structure of mortality, as well as among the causes of disability and deterioration in the quality of life of the population. In this regard, the study of phytopreparations is promising for practical medicine in order to identify new medicinal plants that actively affect metabolic processes to prevent complications of DM, and create new phytopreparations. That drugs could enhance the effect of sulfonamides and potentiate the effect of insulin, thereby reducing the dose of the latter, and it is important for long-term chronic diseases, such as DM. The aim. To study the prospects for the use of phytopreparations in the complex treatment of type 2 diabetes mellitus. Materials and methods. The analytical, logical, generalization methods were used in the work. The analytical method of the study involved deepening the search for phytopreparations and the prospects for their use in the complex treat-ment of type 2 diabetes mellitus and generalization of the data obtained. The logical method of exploratory research of promising phytopreparations was applied in a certain logical sequence, as a result of which the specificity, stage-by-stage and generalization of the relevance of the use of phytopreparations in the complex treatment of type 2 diabetes mellitus was provided for scientific research. The generalizing research method was to determine and prove the characteristics of phytopreparations (analysis and synthesis) and their advantages over synthetic drugs. Results and discussion. The main directions of herbal medicine for DM are associated with reproduction of the effects of insulin, normalization of glucose uptake, stimulation of regeneration of β-cells of the Langerhans islets, elimination of excess glucose from the body – phytopreparations with diuretic properties; elimination of hypoxia – phytopreparations-antihypoxants. In DM, herbal medicine will reduce the frequency of side effects in classical antidiabetic therapy. For any type of diabetes, herbal medicine is prescribed to patients as an improvement in the microcirculation of tissues, normalization of the functions of the cardiovascular and nervous systems, kidneys and eyes. Conclusions. Despite a wide range of drugs used to correct the hemodynamic and metabolic manifestations of the insulin resistance syndrome, they do not fully meet the needs of practical medicine due to the presence of pronounced side effects. In addition, the pharmaceutical market of herbal medicines is very limited and represented mainly by species of medicinal plants, which have certain inconveniences in their use. All this indicates the relevance of the search, creation and introduction of effective and, at the same time, low-toxic drugs based on the medicinal plant raw material into medical practice for the pharmacotherapy of type 2 diabetes and its complications.
Keywords: herbal medicine; medicinal plants; type 2 diabetes mellitus